NETGEN: A Program for Generating Large Scale Capacitated Assignment, Transportation, and Minimum Cost Flow Network Problems - Klingman, D.; Napier, A.; Stutz, J. (Management Science, 1974)
The purpose of this paper is to describe the development, implementation, and availability of a computer program for generating a variety of feasible network problems together with a set of benchmarked problems derived from it. The code “NETGEN” can generate capacitated and uncapacitated transportation and minimum cost flow network problems, and assignment problems. In addition to generating structurally different classes of network problems the code permits the user to vary structural characteristics within a class. Problems benchmarked on several codes currently available are provided in this paper since NETGEN will also allow other researchers to generate identical problems. In particular, the latter part of the paper contains the solution time and objective function value of 40 assignment, transportation, and network problems varying in size from 200 nodes to 8,000 nodes and from 1,300 arcs to 35,000 arcs.